Transport pneumatyczny Poliamidu 6 za pomocą strumienia azotu - Falkowski, Artur (My University, 2014)
W niniejszej pracy przedstawiono propozycję pozbycia się oporów w instalacji transportu pneumatycznego przy produkcji Poliamidu 6 w Grupie Azoty S.A. Zmniejszenie oporów wykaże, czy jest możliwa rozbudowa instalacji transportu pneumatycznego układu dwufazowego gaz-ciało stałe. Rozbudowa polegałaby na zwiększeniu odległości, na które będzie można przetransportować cząstki Poliamidu 6 granulatu wysoko lepkiego przy zastosowaniu azotu.

This thesis shows a suggestion of getting rid of resistance in an installation of pneumatic transport while producing Poliamid 6 in Azoty Group. Reducing resistance will show if it is possible to develop the installation of pneumatic transport of two-phase layout: gas – solid. The development will lie in increasing the distance which particles of Poliamid 6 highly sticky granulate could be transported using nitrogen.
Pneumatic conveying of Polyamide 6 with a stream of nitrogen
Keywords: transport pneumatyczny; azot; cząstka; prędkość; poliamid; pneumatic transport; nitrogen; particle; speed; poliamide